A portion cap rule with two products: An experimental evaluation. (29th May 2022) - Nuño‐Ledesma, José G.
Abstract: Portion cap rules have been proposed to regulate the consumption of foods and ingredients deemed unhealthy. Challenging common intuition, previous theoretical work posits that, when the seller leverages bundling to price‐discriminate, buyers are not necessarily affected and some may even benefit from a quantity restriction. I conduct an experiment designed to test this claim. In the laboratory, human subjects take the role of sellers and offer two products to automated buyers with private preferences. I manipulate the policy environment across treatments. The data largely corroborate the anticipated impacts on consumer surplus, speaking to their robustne ss. In particular, consumers with a low appreciation for the regulated good and a high valuation for the unrestricted item benefit from the cap rule. Résumé: Des règles de plafonnement des portions ont été proposées pour réglementer la consommation d'aliments et d'ingrédients jugés malsains. À l'encontre de l'intuition commune, les travaux théoriques antérieurs postulent que lorsque le vendeur utilise le groupement pour discriminer les prix, les acheteurs ne sont pas nécessairement affectés et certains peuvent même bénéficier d'une restriction de quantité. Je mène une expérience conçue pour tester cette affirmation. En laboratoire, des sujets humains jouent le rôle de vendeurs et proposent deux produits à des acheteurs automatisés ayant des préférences privées. Je manipule l'environnement politique à travers les traitements. Les données corroborent largement les impacts anticipés sur le surplus du consommateur, témoignant de leur robustesse. En particulier, les consommateurs ayant une faible appréciation du bien réglementé et une valorisation élevée de l'article sans restriction bénéficient de la règle de plafonnement.